Reproductive biology of mud crabs (Scylla olivacea) collected from Paikgachha, Khulna, Bangladesh - Paul, Prianka; Islam, Md Sherazul; Khatun, Sumona; Bir, Joyanta; Ghosh, Antara (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study was carried out to estimate the sex ratio, maturity size, gonadosomatic index (GSI), and peak breeding season of mud crabs. Materials and Methods: Samples were collected randomly from the estuary and river of the study area. Sampling was carried out monthly from April to September at every full moon during one high tide. A total number of 240 specimens were sampled, where 53 individuals were hermaphrodite. The crabs were shifted alive to the biology and histology lab for detailed biological study. Sex was determined. Male and female sex ratio and breeding season were also investigated. Results: The male:female ratio was 1:0.96 and the ovarian development was categorized into five stages based on internal observations, viz. immature (stage I), underdeveloped (stage II), early developed (stage III), late developed (stage IV), and mature (stage V). The maturity percentages were 37%, 19%, 13%, 11%, and 20%, respectively. 50% maturation was estimated at 82.36 mm internal carapace width (ICW). The highest mean GSI value was 7.97 ± 3.03. The mature stage was found in all the working periods. This shows that females have activated ovaries in all the working months, and the species are continuous breeders. A higher frequency of vitellogenic ovary and higher GSI value were found in September. The maximum GSI value was found in the size group 70–79 mm. Conclusion: The study shows that the capture from the wild sources of mud crabs without any regulation can threaten the population structure. The capture of female mud crabs should be more than 82.36 mm ICW, which will help conserve and protect young crabs. J. Adv. Vet. Anim. Res., 8(1): 44-50, Mar 2021 http://doi.org/10.5455/javar.2021.h483